2011
DOI: 10.5032/jae.2011.02140
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Barriers Toward Diversity Inclusion Regarding Agricultural Science Teachers in Texas Secondary Agricultural Education Programs

Abstract: This study analyzed Texas secondary agricultural education teachers’ (n = 232) attitudes toward diversity inclusion in Texas secondary agricultural education programs. Using a web–based questionnaire, the researcher employed a nonproportional stratified random sampling technique. Researchers used descriptive statistics to report demographic and personal characteristics and mean scores to assess teachers’ perceptions of the benefits of diversity inclusion, and perceptions of the barriers of diversity inclusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…The relatively few minority members who choose to attend the convention from the very diverse membership of the Belmont FFA chapter highlight the complexity of this issue. Some of these issues were brought forward in this study, such as the lack of FFA members of color at convention, which was similarly echoed in other studies (LaVergne et al, 2011;Roberts et al, 2009). While the students of color from the Belmont FFA chapter recognized this issue and did not view it as a barrier to their participation in FFA, it was still identified and may be a barrier for other urban agriculture students who are not as eager to be involved in FFA.…”
Section: Research Question Three: Negotiating Connections To Ffa Aftementioning
confidence: 82%
See 2 more Smart Citations
“…The relatively few minority members who choose to attend the convention from the very diverse membership of the Belmont FFA chapter highlight the complexity of this issue. Some of these issues were brought forward in this study, such as the lack of FFA members of color at convention, which was similarly echoed in other studies (LaVergne et al, 2011;Roberts et al, 2009). While the students of color from the Belmont FFA chapter recognized this issue and did not view it as a barrier to their participation in FFA, it was still identified and may be a barrier for other urban agriculture students who are not as eager to be involved in FFA.…”
Section: Research Question Three: Negotiating Connections To Ffa Aftementioning
confidence: 82%
“…Research of diverse FFA members also indicated that diverse agriculture students lacked information and roles models in FFA (LaVergne, Larke, Elbert, & Jones, 2011). Junior year members could not readily identify with the rural nature or the leadership possibilities within the organization (Phipps, Osborne, Dyer, & Ball, 2008).…”
Section: Research Question One: Negotiating Connection (Or Lack Therementioning
confidence: 99%
See 1 more Smart Citation
“…students and FFA members interested in FFA activities (LaVergne, Larke, Elbert, & Jones, 2011;Roberts, Hall, Gill, Shinn, Larke, & Jaure, 2009;Warren & Alston, 2007).…”
mentioning
confidence: 99%
“…The context of urban areas provides FFA advisors with unique challenges. Urban and diverse students may lack diverse role models in agriculture and the FFA (LaVergne et al, 2011;Roberts et al, 2009). These students may also lack access or have limited ability to connect with agriculture curriculum and careers (Jones & Bowen, 1998;Talbert & Larke, 1995).…”
mentioning
confidence: 99%